PELAKSANAAN EKSEKUSI OLEH PENGADILAN AGAMA TERHADAP PUTUSAN HAKIM MENGENAI HARTA BERSAMA (STUDI DI PENGADILAN AGAMA BENGKALIS) - Syafira Nurhaliza; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The problem that occurs when the divorce occurs is that one of the parties does not get his rights from the assets that were obtained together during the marriage period as in the Bengkalis Religious Court Decision Number 0613 / Pdt.G / 2017 / PA.Bkls and Pekanbaru High Religious Court Decision No. 20 / Pdt.G / 2019 / PTA.Pbr. The author's interest in taking this title is that the sharing of collective assets needs to be based on aspects of justice for all parties involved. However, not all executions can run smoothly, for example the defendant had bad faith while the trial process was still running, namely transferring the disputed property to a third party.This type of research can be classified in the type of sociological legal research (empirical), because in this study the author directly conducted research at the location or place being studied in order to provide a complete and clear picture of the problem under study. This research was conducted on JalanJend. Sudirman No. 198, Tangkerang Tengah, MarpoyanDamai District, Pekanbaru City, Riau. While the population and samples are Pekanbaru Religious High Court Judges, Attorneys / Lawyers and Parties in litigation. The data sources used are primary data and secondary data. Data collection techniques in this study were interviews, questionnaires, and literature review.The conclusions that can be obtained from the results of the research are First, the basis for the judge in deciding the case for the distribution of joint assets is correct by considering the facts in the trial and the judges' considerations and has fulfilled the sense of justice. The judge in determining joint assets after divorce in the religious court based on decisions is regarding the portion of the distribution of joint assets in the Religious Court. Second, the execution by the Religious High Court of the judge's decision regarding joint assets based on the Bengkalis Religious Court Decision No 20 / Pdt.G / 2019 / PTA.Pbr yet executable. and Third, there are several obstacles in the execution of the distribution of joint assets at the Pekanbaru Religious High Court, which consists of the costs borne by the executioner, the execution officer personnel and the resistance of the execution respondent.Keywords: Execution, Judge's Decision, Joint Assets